THE ESSENCE AND IMPORTANCE OF "PR" IN THE MILITARY SPHERE - Gulnara Khojamuratova (Journals Park Publishing, 2023)
This article describes the PR service, its origin, essence and historical aspects of its formation. At the same time, the features of establishing public relations in the military sphere, the role and significance of this network in defense policy are analyzed.
Keywords: public relations, information, communication, propaganda, national idea, ideology, army, troops, armed forces.